Implementasi model skrip EDS-AV dalam pembelajaran praktik - Edy Sabara; Sabran Sabran (Seminar Nasional LP2M UNM, 2019)
Practical learning is one of the laboratory activities as a means of proving a theory. One of the devices that used in the experiment is the job sheet. Job sheets that are used in general are still in the form of written documents, so it takes a development that can facilitate the practitioner, so that the implementation of the EDS-AV script model in practical learning is being the solution. The purposes of this research were (1) to plan the design of the EDS-AV script model in practical learning in analog electronics practice courses, (2) to motivate students to carry out practices by utilizing EDS-AV script model in practical learning as learning model, and (3) EDS-AV script model can increases student attractiveness in carrying out experiments on job sheets. The development model that used is a combination of several models that have been developed previously and have been modified to be an EDS-AV script model that produces a document in the form of an Audio-Visual based job sheet. The results that obtained based on the description of expert validation data which includes material feasibility aspects, language feasibility aspects, presentation feasibility aspects, aspects of media effects on learning, and overall appearance aspects are all in a very good category. The results obtained in the very good category for the implementation of learning, as well as student responses to the EDS-AV script model in practical learning in the very strong category. The conclusion of the implementation of the EDS-AV model in learning is that the implementation of analog electronic practice learning with the EDS-AV script model has been implemented well, as well as the response of students in general is in the very strong category.